Cassava Plant Soil Processing Machine - Anhar Khalid; Fitria (International Journal of Integrated Science and Technology, 2024)
The cassava tillage machine has a construction design for the frame, plowshares and wheels. In the frame design, the dimensions are ± 1.5 meters long, ± 1 meter wide and ± ½ meter high. For the plowshare design, there is a plowshare size, namely a height of 40 cm, a plowshare width of 38 cm and an angle of ± 35°. And the wheels are made from 16 ring rims with additional outer fins on 40 x 40 mm steel angled profile rims with a thickness of 2 mm. This machine uses a transmission system, namely two transmissions including (pulley with V-belt) and (sprocket with chain) on two shafts that connect each other to rotate the shaft so that the wheels rotate. This machine's transmission uses a type B small pulley with a diameter of 72 mm, a type B large pulley with a diameter of 203.2 mm, a small 420 gear with 14 teeth, and a large 420 gear with 42 teeth. For the V belt, type A belt is available with size 51 inches.